1977
DOI: 10.1111/j.1442-9993.1977.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination studies with Heteropogon contortus

Abstract: Germination characteristics of Heteropogon contortus were investigated in germination cabinets and in the glasshouse using soil trays. Under the former a dual inhibitory system appeared to operate. On the one hand naked caryopses from seeds which were less than 4 months of age were inhibited from germination by a process apparently analogous to epicotyl dormancy. This could readily be broken by applying 1% gibberellic acid and partly broken by repeated wetting and drying. On the other hand between 4 and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…We detected only a weak interaction between year of collection and duration of burial. Tothill (1977) reported high germination of tanglehead seeds stored at room temperature for up to 39 months; our results support this. Two-year old seeds that were buried generally had similar germination responses throughout our 25-mo burial trial as freshly harvested seeds that were buried.…”
Section: T Anglehead (Heteropogon Contortus) Is a Perennial C4supporting
confidence: 81%
See 3 more Smart Citations
“…We detected only a weak interaction between year of collection and duration of burial. Tothill (1977) reported high germination of tanglehead seeds stored at room temperature for up to 39 months; our results support this. Two-year old seeds that were buried generally had similar germination responses throughout our 25-mo burial trial as freshly harvested seeds that were buried.…”
Section: T Anglehead (Heteropogon Contortus) Is a Perennial C4supporting
confidence: 81%
“…A complete understanding of the many factors that affect dormancy (e.g., Wester 1995) is beyond the scope of this study. Tothill (1977) identified two tanglehead dormancy mechanisms: (1) endogenous dormancy that can be relieved by gibberellic acid, and (2) exogenous inhibition associated with seed • 9 appendages. Tothill (1977) showed that appendage (glumes, lemma) removal relieved seed dormancy under laboratory conditions; these appendages, however, were essential to maintenance of seed viability in the field.…”
Section: T Anglehead (Heteropogon Contortus) Is a Perennial C4mentioning
confidence: 99%
See 2 more Smart Citations
“…This subregion has experienced increasing prevalence of tanglehead since the 1990s (Texas Parks and Wildlife Department 2016a; Wester et al 2017). The prevalence of sandy soils and high temperatures in this area provides excellent conditions conducive for the growth of tanglehead (Tothill 1977).…”
Section: Study Areamentioning
confidence: 99%